Efektivitas Pembelajaran Berbasis Schoology - choirudin choirudin (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
Schoology e-learning as one of Learning Management System (LMS). By using schoology aims to show the effectiveness of schoology e-learning through students’ outcome in material quadratic equation. This is achieved when the students’ learning outcomes were taught by schoology e-learning can reach KKM, process skills and students’ activities are better than conventional methods, process skills and students’ activities get a positive effect on students' learning outcomes. This study hypothesis analysis used t-test and linear regression. The results were obtained on experimental class KKM, with the average value of these classes also proved that the experimental class average is better than the control class where control class. Skills process positively to the learning outcomes of mathematics at 24,2%. Having an active students learn mathematics positive about the outcome of 19,8%. Process skills and students active learn mathematics positively to 25,7%.